Evidence of Selection Against Damaged Mitochondria During Early Embryogenesis in the Mouse - Machado, Thiago S.; Macabelli, Carolina H.; Collado, Maite Del; Meirelles, Flávio V.; Guimarães, Francisco E. G.; Chiaratti, Marcos R. (Frontiers in Genetics, 2020)
There is consistent evidence of a purifying filter acting in the female germline to prevent expansion of deleterious mutations in mitochondrial DNA (mtDNA). Given our poor understanding of this filter, here we investigated the competence of the mouse embryo to eliminate dysfunctional mitochondria. Towards that, mitochondria were damaged by photoirradiation of NZB/BINJ zygotes loaded with chloromethyl-X-rosamina (CMXRos). The resultant cytoplasm was then injected into C57BL/6J zygotes to track the levels of NZB/BINJ mtDNA during the preimplantation development. About 30% of NZB/BINJ mtDNA was present after injection, regardless of using photoirradiated or non-photoirradiated cytoplasmic donors. Moreover, injection of photoirradiated-derived cytoplasm did not impact development into blastocysts. However, lower levels of NZB/BINJ mtDNA were present in blastocysts when comparing injection of photoirradiated (24.7% ± 1.43) versus non-photoirradiated (31.4% ± 1.43%) cytoplasm. Given that total mtDNA content remained stable between stages (zygotes vs. blastocysts) and treatments (photoirradiated vs. non-photoirradiated), these results indicate that photoirradiated-derived mtDNA was replaced by recipient mtDNA in blastocysts. Unexpectedly, treatment with rapamycin prevented the drop in NZB/BINJ mtDNA levels associated with injection of photoirradiated cytoplasm. Additionally, analysis of mitochondria-autophagosome colocalization provided no evidence that photoirradiated mitochondria were eliminated by autophagy. In conclusion, our findings give evidence that the mouse embryo is competent to mitigate the levels of damaged mitochondria, which might have implications to the transmission of mtDNA-encoded disease.